PARTICIPATORY MAPPING : - Makailipessy, Marvin Mario; Abrahamsz, James; Tubalawony, Simon (Pattimura University, 2023)
Participatory mapping techniques are a way to facilitate the rapid collection of data and information at the community level. The Aru Islands, which have a considerable coastal resource potential, need to be supported by rapid data collection in support of sustainable management of coastal areas. Strengthening the local community in Aru is very much needed in terms of gathering such data through participatory mapping. The purpose of this participatory mapping is to identify the potential and utilization of space. In accordance with the entire phase of the process, a map of the fish species is produced which are potentially captured; the crustaceans which have economic value, the river streams of mega species and the locations which are the green turtle breeding areas, as well as three types of space utilization.